The Effect Of Product Quality And Service Quality On Customer Satisfaction At Heri Manna Photocopy Shop, South Bengkulu Regency - Anggriani, Tiara Dwi; Made E. G, Ida Ayu; Wagini, Wagini (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
A photocopier is a tool for recopying documents or illustrations using light, heat, chemicals or static electric charges. Photocopy machines continue to be improved to meet people's needs, starting from black and white photocopies to color photocopies that resemble the original. The purpose of this research is to prove that product quality and service quality influence customer satisfaction at Heri Manna Photocopy, South Bengkulu. This type of research uses quantitative research. The analytical method in this research uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, Coefficient of Determination, and hypothesis testing using the t test. The number of samples studied was 90 Heri Photocopy consumers. The results of the multiple linear regression analysis are the equation: Y = 13.152 + 0.477 ) at Heri Photocopy, South Bengkulu Regency. The value of the coefficient of determination from the calculation results using SPSS can be seen from the coefficient of determination from R square of 0.851. This means that the product quality value (X1) and service quality value (X2) influence customer satisfaction (Y) by 85.1% while the remaining 14.9% is influenced by other variables not examined in the research. So product quality and service quality have a very significant influence on customer satisfaction.